2019
DOI: 10.1007/s10071-019-01265-2
|View full text |Cite
|
Sign up to set email alerts
|

Cats match voice and face: cross-modal representation of humans in cats (Felis catus)

Abstract: We examined whether cats have a cross-modal representation of humans, using a cross-modal expectancy violation paradigm originally used with dogs by Adachi et al. (2007). We compared cats living in houses and in cat cafés to assess the potential effect of postnatal experience. Cats were presented with the face of either their owner or a stranger on a laptop monitor after playing back the voice of one of two people calling the subject's name. In half of the trials the voice and face were of the same person (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
5
24
3
Order By: Relevance
“…Regarding the heterospecific emotional signals, we found that cats correctly matched the human auditory and visual signals of "happiness" and "anger", suggesting that they have a cognitive representation of these emotions, which allow cats to discriminate between them. This is in line with recent findings about cats' ability to cross-modally recognize humans [35]. Moreover, our results are consistent with previous studies demonstrating that cats are sensitive to human communicative cues [10,50] and to their emotions, particularly if expressed by their owners [16,42].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the heterospecific emotional signals, we found that cats correctly matched the human auditory and visual signals of "happiness" and "anger", suggesting that they have a cognitive representation of these emotions, which allow cats to discriminate between them. This is in line with recent findings about cats' ability to cross-modally recognize humans [35]. Moreover, our results are consistent with previous studies demonstrating that cats are sensitive to human communicative cues [10,50] and to their emotions, particularly if expressed by their owners [16,42].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a growing body of literature has demonstrated that domestic species recognize human faces (dogs: [5]; sheep: [22,23]; horses: [24]) and voices (cats: [3]; horses: [20,21]; pig: [19,25]; and dogs: [26]). Animals not only identify conspecifics and humans through separate sensory modalities (e.g., cats: [3]; dogs: [5]; goats: [27]; sheep: [22,23]; cattle: [6]; and cheetahs: [28]) but they are also capable of integrating identity cues from multiple sensory modalities to recognize them (dogs: [26,29]; horses: [30,31]; goats: [32]; rhesus monkeys: [2,33]; crows: [34], and cats: [35]). This high-level cognitive ability demonstrates that animals form a multimodal internal representation of individuals that is independent of the sensory modality [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are animals biased towards paying attention to animacy, there is also a widespread capacity to learn patterns and develop implicit cross-modal expectations regarding how the animate entities in one's surroundings typically behave (Adachi et al 2007;Proops et al 2009;Takagi et al 2019). This also has high survival value, since it can allow an animal to predict the behaviour of friends and foe, as well as detect anomalous behaviour.…”
Section: Prerequisites For a Codmentioning
confidence: 99%
“…Although cats have not been clearly selected for different work tasks, as in the case of dogs (Coppinger and Schneider 1995;Gácsi et al, 2009), the need for a smooth coexistence with humans as companions could be a strong enough selective pressure on some of the socio-cognitive capacities of cats to become analogous to the ones seen in dogs. Indeed, researchers found that cats show similar performance to dogs in various tasks, for example in two-way object choice tasks, they follow proximal and distal pointing signals (Miklósi et al 2005;human gazing, Pongrácz et al 2019); they rely on their owner's reaction when encountering unfamiliar objects (Merola et al 2015); and they can recognize their owners' voice (Saito and Shinozuka 2013;Takagi et al 2019); as well as their own name (Saito et al 2019). However, thus far, the only paper where the effect of human ostensive signals on cats was tested, showed a minimal effect only-the performance of cats in a gaze-following test was not affected by the presence or absence of ostensive signals, only the speed of establishing eye contact with the subject was enhanced by the ostensive cues (Pongrácz et al 2019).…”
Section: Introductionmentioning
confidence: 99%